Plataforma web de apoyo para la asignación, entrega y calificación de guías y actividades para la Institución Educativa Internado Indígena San José de Uribia (2022)
In educational institutions it is already a necessity to have virtual platforms so that students can access from home or wherever they are to download their digital support material for their activities during the school year. For this reason, the rector of the Intenado Indígena San José de Uribia Educational Institution was motivated to implement a web platform where the teacher uploads the course material and the students can access it digitally. This will reduce the cost of printing and photocopying support material. This document shows the development of an educational virtual platform for the reception of guides and activities of the school. The methodology used for the development was SCRUM.